Single-Cell Imaging Reveals That Staphylococcus aureus Is Highly Competitive Against Pseudomonas aeruginosa on Surfaces - Niggli, Selina; Wechsler, Tobias; Kümmerli, Rolf (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa and Staphylococcus aureus frequently occur together in polymicrobial infections, and their interactions can complicate disease progression and treatment options. While interactions between P. aeruginosa and S. aureus have been extensively described using planktonic batch cultures, little is known about whether and how individual cells interact with each other on solid substrates. This is important because both species frequently colonize surfaces to form aggregates and biofilms in infections. Here, we performed single-cell time-lapse fluorescence microscopy combined with automated image analysis to describe interactions between P. aeruginosa PAO1 with three different S. aureus strains (Cowan I, 6850, JE2) during microcolony growth on agarose surfaces. While P. aeruginosa is usually considered the dominant species, we found that the competitive balance tips in favor of S. aureus on surfaces. We observed that all S. aureus strains accelerated the onset of microcolony growth in competition with P. aeruginosa and significantly compromised P. aeruginosa growth prior to physical contact. Upon direct contact, JE2 was the most competitive S. aureus strain, simply usurping P. aeruginosa microcolonies, while 6850 was the weakest competitor itself suppressed by P. aeruginosa. Moreover, P. aeruginosa reacted to the assault of S. aureus by showing increased directional growth and expedited expression of quorum sensing regulators controlling the synthesis of competitive traits. Altogether, our results reveal that quantitative single-cell live imaging has the potential to uncover microbial behaviors that cannot be predicted from batch culture studies, and thereby contribute to our understanding of interactions between pathogens that co-colonize host-associated surfaces during polymicrobial infections.